The earliest data on the medieval thombstones stećci in northern Bosnia: chronology and contextualisation - Rabić, Nedim (Historical Thought, 2025)
This paper emphasizes an importance of the document from 1725, which was so far neglected in the historiography of the Bosnian medieval tombstones - stećci. It is a report written after the establishment of the border between the Habsburg Monarchy and the Ottoman Empire as a result of the Treaty of Passarowitz in 1718. Although very brief, this document undoubtedly indicates the existence of a necropolis of stećcitombstones in Bijeljina, or its immediate vicinity, as well as in the area of the settlement of Kobaš on banks of the river Sava. After the mention of stećci in the travelogue of Benedikt Kuripešić in 1530, these data represent the second oldest mention of these medieval tombstones in written sources, and per se deserve attention. There are indications that the monuments mentioned in this report, or at least some of them, could be linked to those stećci that were ‘’sensationaly’’ discovered in 2002 at the foundations of the demolished Atik mosque in Bijeljina.